The Internet in China - Choy, Pinky D.W.; Cullen, Richard (Columbia Journal of Asian Law, 1999)
The impact ofthe Interet on all spheres of life, political, commercial, and social, has been very significant. This impact is still growing at a extraordinary rate and few are game to predict exactly where these developments will lead. This is a rather special sort of communications revolution, however. Unlike television and radio, for example, the Internet combines remarkable changes in mass communication and in person-to- person communications in a single technology, and it does so in ways that are far less expensive (and much faster) than its long standing competitors. It is now clear that modem trade and commerce must increasingly be linked into this system to compete. This truth is even more evident when one considers research and development. For a country like China, which regards modernization as a near absolute fundamental value, the allure of the Internet is immense. But China is also still the largest One Party State, by far, that the world has ever seen. Although Marxism, as an economic doctrine, is largely a spent force in China, Leninism is alive and well. It remains the keystone of political structure theory in the People’s Republic of China (PRC). A fundamental tenet of Leninism is the requirement that the state must control the media. The metaphor often used is that the media must be both the “throat and tongue” and “the eyes and ears” of the party.